Uji Toksisitas Sub Akut Iunfusa Daun Afrika (Vernonina amygdalina Del.) terhadap Histopatologi Ginjal Mencit Galur Balb/C - Nida Faradisa; Nurul Marfu'ah; Surya Amal (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2018)
Alloh created everything in this universe to take benefit from it, including African Leaf plant. One of the benefits of this leaf is to treat diabetes mellitus, malaria and dysentery. African leaf contains saponin type compounds, flavonoids and steroid glycosides. Drugs that enter the body will go through the phase of metabolism in the liver and excretion in the kidneys. Kidney that serves to dispose of metabolic waste and body toxins in the form of urine. The purpose of this research is to know the effect of African Leaf infusion on histopathology of mice kidney BALB/c. Samples in the form of BALB / c male strain of mice were 12 samples were divided into 4 treatment types with 3 replications. Treatment of control (aquades), African leaf infusion 10% b/v, 20% b/v and 30% b/v infused orally for 28 days. The data obtained were analyzed by Kruskall Wallis test and the data shows congestion value 0.241 > p 0.05 and hemorragic value 0.070 > p 0.05 which means there is no significant difference between treatment types. Therefore, it can be concluded that African leaf infusion has no effect on histopathology of renal mice BALB/c. However, the trend of results in this study indicates that the increased dose given to mice can reduce congestion and hemorrhage in the kidneys